How Does the Covid-19 Pandemic Affect the Learning Process of IPS Subjects at the Primary School Level in Indonesia? - Kamila, Lula Najwa; Anggraeni, Andi Annisa; Nurjanah, Arum; Fadilah, Dwi Diah; Wahyunengsih, Wahyunengsih (Universitas Pahlawan Tuanku Tambusai, 2024)
Since President Joko Widodo announced the first COVID-19 case in Indonesia in March 2020, the country has faced a prolonged pandemic, officially ending in June 2023. This period saw significant transformations across various sectors, particularly in education. The COVID-19 pandemic necessitated a shift to online learning, presenting numerous challenges such as limited student understanding, inadequate facilities, teacher proficiency in technology, and access issues. These challenges highlighted gaps in the national education system as outlined in the Law of the Republic of Indonesia Number 20 of 2003. This study employs a qualitative, descriptive approach through literature review to explore the impact of the pandemic on elementary social studies education in Indonesia. Data collection involved extensive review of secondary sources, including books, scientific articles, and research reports. The analysis focused on the COVID-19 pandemic's influence on the learning process, revealing significant challenges and proposing solutions such as optimizing learning media, fostering collaboration between teachers and parents, and creating contextual learning modules. The study underscores the necessity for improved digital infrastructure, enhanced digital capabilities, and government support to ensure effective and efficient online education. The findings contribute to understanding the broader implications of the pandemic on education and propose strategies for the future in.